2000
DOI: 10.2116/analsci.16.621
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Photolytical Transformation Products of Pentachlorophenol in Water

Abstract: The photodegradation of pentachlorophenol in water was examined with a high-pressure mercury lamp. A number of photodegradation products of pentachlorophenol, such as less-chlorinated phenols through reductive dechlorination, and catechol and trihydroxylated products via the addition of hydroxyl radicals, were observed as major products. Moreover, polychlorinated biphenylethers, hydroxylated polychlorobiphenylethers and polychlorinated dibenzo-p-dioxins as minor products were also formed by dimerization proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…The results show that the PCP dechlorination pathway can be tracked from the GC-MS analysis. Similar to the results of previously reported by Piccininia et al (1998), Hong et al (2000, Suegara et al (2005). Therefore, this mixed culture may be used for bioremediation of PCP containing wastewater from pulp paper mill, pharmaceuticals, pesticides and agro based industries.…”
Section: Gc-ms Analysissupporting
confidence: 88%
“…The results show that the PCP dechlorination pathway can be tracked from the GC-MS analysis. Similar to the results of previously reported by Piccininia et al (1998), Hong et al (2000, Suegara et al (2005). Therefore, this mixed culture may be used for bioremediation of PCP containing wastewater from pulp paper mill, pharmaceuticals, pesticides and agro based industries.…”
Section: Gc-ms Analysissupporting
confidence: 88%
“…Therefore, it is assumed that 235T3CP and 236T3CP are dechlorination reaction products of 2356T4CP, and that 234T3CP is a de-chlorination reaction product of 2346T4CP. This research itself does not identify such T3CP products, but 235T3CP is reported as an ultraviolet decomposition product of PCP (Hong et al 2000). The atomic charge value of 235T3CP is highest at position 3, which suggests that 25D2CP will be generated as a by-product.…”
Section: Resultsmentioning
confidence: 79%
“…Reports have been made on the photodecomposition and removal efficiency of each organochlorine compound, on the identification of intermediate products during photodecomposition, and on the design of the treatment equipment required by the method (Hong et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxylated diphenyl was formed as precursors of dioxins during photolysis and pyrolysis of chlorophenols in our previous report. 27 Hydroxylated dichlorodibenzodioxin and furans were also observed.…”
Section: Identification Of Electrical Degradation Products Of 4-chlormentioning
confidence: 97%
“…27 Mass spectra of their TMS derivatives were characterized by the presence of their molecular ion, [M-15] + , [M-OTMS + H] + ion and their distribution of 37 Cl isotope ions. In EI, they yielded intense molecular ions because of their rigid and aromatic planar structure.…”
Section: Identification Of Electrical Degradation Products Of 4-chlormentioning
confidence: 99%